Islamic Education in Nusantara at Mosques (Review of Historical and Contemporary Aspects) - Nufus, Dita Durotun; Safuri, B; Kultsum, Umi (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Since the time of the Islamic kings, mosques have become the center of Islamic activities throughout the Archipelago. Mosques function as educational institutions, centers for spiritual growth, and social interaction within the community, in addition to being places of worship. The purpose of this research is to evaluate the role of mosques in Islamic education in the Archipelago from both historical and modern perspectives. The study's findings indicate that mosques have played an important role in the lives of Muslims as centers of social interaction, education, and conversation in addition to being places of worship. Mosques have now evolved into more comprehensive activity centers that encompass outreach, social, health, and educational services. This evolution shows how mosques can be flexible and adapt to the needs of the community and the changes of the times.